Firm Size and Firm Value in Manufacturing Companies Listed on The Indonesia Stock Exchange: Does Profitability Mediate The Relationship? - Elly Lestari; Yuni Setyawati; Sri Indah; Hirdinis Hirdinis; Manuel Goncalves (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Firm value is a measure of an investor's opinion of a business's overall performance and is frequently directly related to stock prices. Increased market trust in the company's future potential as well as its present performance might result from a strong firm value.Purpose: Research objective is to confirm the effect of company size -listed on the Indonesia Stock Exchange within the manufacturing sector- on the firm value. Furthermore, this study also investigate the role of profitability as an intervening factor. Design/methodology/approach: The focus of the investigation is on the manufacturing firms that have disclosed their financial reports up to the year 2018. To ensure a comprehensive sample for research purposes, we selected a saturated sample of 14 firms from this population, resulting in 98 observations. Path analysis is employed to test the hypotheses. Finding/Result: The research findings indicate that company size exerts both a direct and indirect influence on firm value, with profitability acting as a moderating factor in this relationship. Specifically, an increase in profitability has a positive impact on a company's value. Conclusion: The size of a business can enhance investor confidence, as larger companies are typically more visible and accessible sources of information, and” they have the potential to achieve greater profitability, consequently contributing to their overall value.Originality/Value: Profitability acts as a crucial mediator that enhances our understanding of how firm size influences firm value. Keywords: firm size, profitability, firm value, Indonesia Stock Exchange, manufacturing companies